2018
DOI: 10.1007/s10802-018-0425-7
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Evaluating School-Based Mindfulness Intervention for Ethnic Minority Youth: Exploring Mediators and Moderators of Intervention Effects

Abstract: The study examined the efficacy of a school-based mindfulness intervention on mental health and emotion regulation outcomes among adolescents in a wait-list controlled trial. The study also explored mediators and moderators of intervention effects. A total of 145 predominantly ethnic minority (Asian and Latino) 9th grade students with elevated mood symptoms were randomized to receive a 12-week mindfulness intervention at the start of the academic year, or in the second semester of the year. Students completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 97 publications
5
55
0
Order By: Relevance
“…79 Nevertheless, this study result was contradictory to previous studies which demonstrated that mindfulness training reduced expressive suppression in clinical and non-clinical populations. [80][81][82] Meanwhile, recent studies have suggested that emotion regulation practices and the associated psychological impacts are culturally specific. 81 Contradictory to the Western context which values emotional expression, the Asian culture considers the expression of the inner self as ego-focused, and a disturbance of social harmony.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…79 Nevertheless, this study result was contradictory to previous studies which demonstrated that mindfulness training reduced expressive suppression in clinical and non-clinical populations. [80][81][82] Meanwhile, recent studies have suggested that emotion regulation practices and the associated psychological impacts are culturally specific. 81 Contradictory to the Western context which values emotional expression, the Asian culture considers the expression of the inner self as ego-focused, and a disturbance of social harmony.…”
Section: Discussionmentioning
confidence: 99%
“…[80][81][82] Meanwhile, recent studies have suggested that emotion regulation practices and the associated psychological impacts are culturally specific. 81 Contradictory to the Western context which values emotional expression, the Asian culture considers the expression of the inner self as ego-focused, and a disturbance of social harmony. 83 Suppression may function as adaptive self-restraint and interpersonal harmony in the Asian contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, analyses specifically examining the effects of mindfulness interventions in schools suggests that they are effective at improving cognitive performance, mental health, and wellbeing as well as reducing stress (Carsley, Khoury, & Heath, 2017; Zenner, Herrnleben-Kurz, & Walach, 2014). Overall, these programs are well-liked by adolescents, and also result in increases in both emotion-regulation and self-regulation as well as reductions in stress, depression, externalizing behaviors, and sleep problems (Bluth et al, 2016; Broderick & Metz, 2009; Dvorakova et al, 2017; Eva & Thayer, 2017; Fung, Guo, Jin, Bear, & Lau, 2016; Fung et al, 2018; Metz et al, 2013; Shomaker et al, 2017). …”
Section: The Benefits Of Increasing Mindfulness In Adolescencementioning
confidence: 99%
“…L2B, however, was specifically tailored to meet the developmental needs of adolescents (i.e., supporting empowerment, autonomy, and self-efficacy in the face of stress; building skills for emotion regulation; encouraging group cohesion by focusing on the common experiences of adolescence; reducing tendencies for social comparison and self-judgment; and encouraging peer acceptance and support via shared practice and activities). This program is very well-liked by adolescents, increases mindfulness, and promotes emotion regulation as well as reduces stress, depression, and externalizing behaviors (Bluth et al, 2016; Broderick & Metz, 2009; Dvorakova et al, 2017; Eva & Thayer, 2017; Fung et al, 2016; Fung et al, 2018; Metz et al, 2013; Shomaker et al, 2017). Therefore, our team has selected L2B has the mindfulness program to use as the foundation for an EMI supplement.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…The mindfulness method uses a series of exercises designed to train the mind to stay focused and open to standard conditions, including stressful situations (Fung et al, 2019). Other research states that a person who scores high on mindfulness shows high selfdisclosure and can make a better emotional assessment of adolescents, mindfulness is found to reduce the adverse effect on adolescents entering adulthood (Sultan, 2018).…”
Section: Introductionmentioning
confidence: 99%